KONTRIBUSI SIKAP DISIPLIN TERHADAP KEMANDIRIAN BELAJAR SISWA DI SEKOLAH DASAR - Yudhie Suchyadi; Oding Sunardi; Lina Novita (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2020)
CONTRIBUTION OF DISCIPLINE ATTITUDES TOWARD STUDENT LEARNING INDEPENDENCE IN PRIMARY SCHOOLSThe research objective is to examine the contribution of disciplinary attitudes to learning outcomes indirectly through student independence. Type of quantitative research. The sampling technique used proportional random sampling. Data collection techniques using questionnaires and documentation. The data analysis technique used path analysis. The results of the study with a disciplined attitude, simultaneously contribute to independence. Partially, the attitude of discipline and learning facilities does not directly contribute to learning outcomes and indirectly contribute positively through independence. Partially, discipline affects independence by 4.28%. Learning facilities affect independence by 16.73%.